2014
DOI: 10.1186/s12909-014-0260-7
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine trainees’ clinical experience of chronic disease during training: a cross-sectional analysis from the registrars’ clinical encounters in training study

Abstract: BackgroundA broad case-mix in family physicians’ (general practitioners’, GPs’) vocational trainee experience is deemed essential in producing competent independent practitioners. It is suggested that the patient-mix should include common and significant conditions and be similar to that of established GPs. But the content of contemporary GP trainees’ clinical experience in training is not well-documented. In particular, how well trainees’ experience reflects changing general practice demographics (with an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
2
13
1
Order By: Relevance
“…This level of registrar engagement has not always been evident in other ReCEnT analyses. Analyses of continuity of care in registrars’ consultations, and of consultations with older patients and patients with chronic disease, have suggested limited therapeutic engagement in these areas . This analysis’ finding of a non‐significant trend for older patient age being associated with less dietitian/nutritionist referral than middle‐aged patients (despite increasing diet‐related morbidity with age) may reflect a general lack of engagement with the management of older patients, being evident also in diet‐related aspects of health.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This level of registrar engagement has not always been evident in other ReCEnT analyses. Analyses of continuity of care in registrars’ consultations, and of consultations with older patients and patients with chronic disease, have suggested limited therapeutic engagement in these areas . This analysis’ finding of a non‐significant trend for older patient age being associated with less dietitian/nutritionist referral than middle‐aged patients (despite increasing diet‐related morbidity with age) may reflect a general lack of engagement with the management of older patients, being evident also in diet‐related aspects of health.…”
Section: Discussionmentioning
confidence: 89%
“…They are entering practice and establishing future clinical behaviour at a time when the multidisciplinary team approach in general practice is becoming well‐accepted. A study of Australian GP registrars found that, compared to their established GP colleagues, a considerably smaller proportion (30%) of consultations included a chronic disease . However, there are no data on registrar dietetic referrals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient‐based interview and survey data suggest that older patients may treat GPR consultations as a stop‐gap measure, for example for a prescription repeat, until they can consult their regular GP to address management concerns . In addition, it appears that patients’ desire to keep chronic disease management with their regular GP increases with the complexity of older patients’ health problems , supported by data demonstrating reduced rates of consultation between GPRs and patients with chronic disease in comparison with established GPs .…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings accord with themes of trust and continuity of care from other Australian studies. 2,4,19,24 Thus, the study offers insights into the challenges for a shared-care approach to aged care management in general practice.…”
Section: Study Limitationsmentioning
confidence: 99%